2001
DOI: 10.1074/jbc.m107250200
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional Profiling Reveals Global Defects in Energy Metabolism, Lipoprotein, and Bile Acid Synthesis and Transport with Reversal by Leptin Treatment in Ob/ob Mouse Liver

Abstract: Leptin, a hormone secreted by adipose tissue, has been shown to have a major influence on hepatic lipid and lipoprotein metabolism. To characterize changes in lipid and lipoprotein gene expression in mouse liver, suppression subtractive hybridization and cDNA microarray analysis were used to identify mRNAs differentially expressed after leptin treatment of ob/ob mice. Ob/ob mice showed a profound decrease in mRNAs encoding genes controlling bile acid synthesis and transport as well as a variety of apolipoprote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
107
1

Year Published

2002
2002
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 145 publications
(116 citation statements)
references
References 54 publications
8
107
1
Order By: Relevance
“…Increases in reactive oxygen species are prevented by SOD2 [28]. Impaired expression of SOD2 or other genes associated with a stress defence system, including FMO5, as observed here and in ob/ob mice [11], could increase oxidative stress in the diabetic state. Similar alterations in gene expression in blood vessels may increase the risk of atherosclerosis.…”
Section: Discussionmentioning
confidence: 51%
See 3 more Smart Citations
“…Increases in reactive oxygen species are prevented by SOD2 [28]. Impaired expression of SOD2 or other genes associated with a stress defence system, including FMO5, as observed here and in ob/ob mice [11], could increase oxidative stress in the diabetic state. Similar alterations in gene expression in blood vessels may increase the risk of atherosclerosis.…”
Section: Discussionmentioning
confidence: 51%
“…The down-regulation of plasminogen observed by us in the diabetic liver could thus result in reduced fibrinolysis, leading to thrombosis and atherosclerosis. Down-regulation of plasminogen has also been reported in the livers of ob/ob mice [11].…”
Section: Discussionmentioning
confidence: 86%
See 2 more Smart Citations
“…Thus, it was suggested that oestrogen down-regulates ketogenesis and activates sterol synthesis. This effect of oestrogen is the reverse of the effect of leptin (Liang & Tall 2001), and the overall gene expression changes by oestrogen contrasted significantly with the gene expression changes caused by leptin. Although not all gene expression profiles are consistent with an oestrogen effect (for example, urea metabolism was not affected in our study though it was affected by leptin), the behaviour of the selected genes in our study showed the reverse effect following leptin treatment.…”
Section: Discussionmentioning
confidence: 82%